2017
DOI: 10.1002/acm2.12105
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations of linear accelerator‐based frameless extracranial radiosurgery for treatment of occipital neuralgia for nonsurgical candidates

Abstract: Occipital neuralgia generally responds to medical or invasive procedures. Repeated invasive procedures generate increasing complications and are often contraindicated. Stereotactic radiosurgery (SRS) has not been reported as a treatment option largely due to the extracranial nature of the target as opposed to the similar, more established trigeminal neuralgia. A dedicated phantom study was conducted to determine the optimum imaging studies, fusion matrices, and treatment planning parameters to target the C2 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…According to the criteria of the IHS proposed in 2004 [ 20 ], CGH diagnosis requires radiological evidence. We obtained GON tractography with reliability and performed a quantified analysis using DTI parameters from the C2-C3 DRG and GON, which were considered vulnerable to neuropathy in CGH [ 21 , 22 ]. We found that the DTI parameter of the FA value for the C2 DRG can be used for detecting severe headaches with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the criteria of the IHS proposed in 2004 [ 20 ], CGH diagnosis requires radiological evidence. We obtained GON tractography with reliability and performed a quantified analysis using DTI parameters from the C2-C3 DRG and GON, which were considered vulnerable to neuropathy in CGH [ 21 , 22 ]. We found that the DTI parameter of the FA value for the C2 DRG can be used for detecting severe headaches with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…During paroxysmal attacks, muscle contracture may occur, associated with residual pain (VAS: 5.4) 5,6,8‐10 , triggering points on the nerves 5 . Pain can be temporarily controlled by an anesthetic block of the affected nerve 7‐14 . Most cases are idiopathic, but secondary forms may result from trauma (C2 nerve root or ganglion compression), anatomical disorders (entrapment by hypertrophic atlanto‐epistropic ligament), degenerative causes (atlantoaxial subluxation in rheumatoid arthritis), infection (neurosyphilis), and tumors (multiple myeloma), as well as painful (polymyalgia rheumatica) and hormonal (acromegaly) syndromes 8,11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…block of the affected nerve [7][8][9][10][11][12][13][14] . Most cases are idiopathic, but secondary forms may result from trauma (C2 nerve root or ganglion compression), anatomical disorders (entrapment by hypertrophic atlanto-epistropic ligament), degenerative causes (atlantoaxial subluxation in rheumatoid arthritis), infection (neurosyphilis), and tumors (multiple myeloma), as well as painful (polymyalgia rheumatica) and hormonal (acromegaly) syndromes 8,[11][12][13] .…”
mentioning
confidence: 99%
See 1 more Smart Citation